2020
DOI: 10.1002/cem.3317
|View full text |Cite
|
Sign up to set email alerts
|

N‐BANDS: A new algorithm for estimating the extension of feasible bands in multivariate curve resolution of multicomponent systems in the presence of noise and rotational ambiguity

Abstract: A new algorithm named N‐BANDS has been developed for the estimation of the combined effect of noise and rotational ambiguity in the bilinear decomposition of data matrices using the popular multivariate curve resolution–alternating least‐squares model. It is based on a nonlinear maximization and minimization of a component‐wise signal contribution function (SCF), with a single‐objective function and a separate module for applying a variety of constraints. The algorithm can be applied to multicomponent systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Because the present experimental data are rather noisy, negative entries occur in the data matrices, and thus, it is important to consider how the available algorithms for computing the band boundaries handle these negative values. The recently published N‐BANDS method was adopted here, because it provides nonnegative component profiles and consistent results for increasing levels of noise 24 . N‐BANDS can be adapted to minimize or maximize any of the three parameters mentioned above.…”
Section: Numerical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the present experimental data are rather noisy, negative entries occur in the data matrices, and thus, it is important to consider how the available algorithms for computing the band boundaries handle these negative values. The recently published N‐BANDS method was adopted here, because it provides nonnegative component profiles and consistent results for increasing levels of noise 24 . N‐BANDS can be adapted to minimize or maximize any of the three parameters mentioned above.…”
Section: Numerical Studiesmentioning
confidence: 99%
“…The analysis of a typical test sample included the following activities: (1) joining the test sample data matrix with those for the calibration samples along the time decay direction (this is the mode representing component concentrations), building an augmented data matrix of size 12,023 data points, (2) decomposing the augmented matrix using multivariate curve resolution–alternating least‐squares (MCR‐ALS) 25 under the constraints of nonnegativity and sample selectivity (also called species correspondence), and (3) using the retrieved spectral and time decay profiles as starting values for N‐BANDS estimation of band boundaries 24 …”
Section: Numerical Studiesmentioning
confidence: 99%
“…[1]. It is also possible to approximate the boundaries with two extreme profiles estimated by either the MCR-BANDS [9,10] or N-BANDS [11] algorithms, corresponding to maximum and minimum values of the so-called signal contribution function. In particular, it was recently found that N-BANDS is able to reasonably approximate these boundaries of the feasible solutions in the presence of noise [12].…”
Section: Introductionmentioning
confidence: 99%
“…8 In view of the above, it is imperative to bridge the gap between the body of theoretical work on rotational ambiguity in bilinear decomposition on one side, and experimental analytical protocols based on second-order multivariate calibration on the other. Especially useful in this regard are two recently introduced models: N-BANDS 9 ("N" stands for noise) and sensor-wise N-BANDS (SW-N-BANDS). 10 The former permits the estimation of the uncertainty in analyte concentration produced by rotational ambiguity, and the latter provides qualitative information for the correct interpretation of the component profiles retrieved by bilinear decomposition.…”
Section: Introductionmentioning
confidence: 99%